Discontinuity in Prior English Learning and Its Impact on Seventh Graders’ Motivation - Lyza Yustika; Lidwina Sri Ardiasih; Widya Rizky Pratiwi (Juliet, 2025)
This study examines how discontinuity in prior English learning, rooted in the Kurikulum Merdeka policy, affects the motivation and engagement of seventh-grade students in East Bintan, Indonesia. Under Kurikulum Merdeka, English is not compulsory at the elementary level, leading to uneven preparedness when students transition to junior high school. A qualitative case study was conducted through classroom observations, questionnaires, and interviews with students and English teachers. Findings reveal that students with prior exposure to English demonstrated greater confidence and persistence, while those without such experience reported anxiety, low self-efficacy, and reluctance to engage. Teachers also struggled to balance instruction due to the wide gap in readiness. The results indicate that discontinuity not only hampers academic performance but also undermines emotional and behavioral motivation. The study concludes that bridging strategies, such as differentiated instruction, remedial support, and teacher professional development, are essential to mitigate the motivational gaps created by curriculum discontinuity.